Community poultry farmer knowledge, attitudes and practices contributing to antimicrobial resistance in high density areas of Bulawayo, Zimbabwe - Ndlovu, Patience (Stellenbosch : Stellenbosch University, 2024)
Thesis (MSc)--Stellenbosch University, 2024.